Taxonomic revision of the flavopalliata species group of Signiphora (Hymenoptera: Signiphoridae) - Woolley, J. B.; Molin, A. Dal (Zootaxa, 2017)
The flavopalliata species group of Signiphora Ashmead (Hymenoptera: Signiphoridae) is revised. Twelve species are redescribed: Signiphora aleyrodis Ashmead, S. aspidioti Ashmead, S. borinquensis Quezada et al., S. coquilletti Ashmead, S. fax Girault, S. flavella Girault, S. flavopalliata Ashmead, S. lutea Rust, S. maculata Girault, S. merceti Malenotti, S. perpauca Girault and S. xanthographa Blanchard. Signiphora townsendi Ashmead is synonymized under S. aleyrodis n. syn.; Thysanus insularis Dozier and S. flavopalliata desantisi De Santis are synonymized under S. fax n. syns.; S. basilica Girault, S. euclidi Girault, S. flava Girault, S. caridei Brèthes, S. thoreauini Girault and Thysanus louisianae Dozier are synonymized under S. flavella n. syns.; and S. woolleyi Hayat is synonymized under S. perpauca n. syn. Thirteen new species are described: S. bennetti n. sp., S. biloba n. sp., S. brachyptera n. sp., S. curepensis n. sp., S. dozieri n. sp., S. ehleri n. sp., S. ensifera n. sp., S. falcata n. sp., S. jojobae n. sp., S. longitibia n. sp., S. plaumanni n. sp., S. renuncula n. sp. and S. tridentata n. sp. Lectotypes are designated for S. aleyrodis, S. townsendi, S. fax, S. flavella, S. occidentalis, S. lutea, S. maculata and S. xanthographa.